Dramatic changes in urban morphology: urban regeneration in Istanbul-Gaziosmanpasa - Erkan Yazıcı, Yasemin; Gökşin, Zeynep Ayşe; TÖRE, EVRİM ÖZKAN (International Seminar on Urban Form (ISUF), 2016)
In Turkey, urban planning is being replaced by piecemeal and property-led urban regeneration projects. Those urban regeneration projects affect cities in Turkey in two fundamental ways. The first impact is on the morphology and the second impact is on the social structure of the city. In this paper, their impact on the morphology of the city is analyzed through a case study of Istanbul’s Gaziosmanpaşa District. There are squatter houses from 1950s and apartment blocks redeveloped from squatter houses in the urban regeneration area designated by central and local governments. Today, these buildings have become the subject of regeneration. The paper is based on the preliminary findings of a TUBITAK-funded (The Scientific and Technological Research Council of Turkey) project being developed by the authors. As well as literature review, the research is shaped by face-to-face interviews with related agency representatives, on-site observations, analysis of plans, projects and documents prepared by related agencies and articles in the media on the subject. The main findings of the research established that the existing urban morphology of the area, formed by low-rise, single houses in an organic and unplanned setting, was changing. This existing urban fabric is being replaced by high-rise apartment blocks which can be described as gated communities. As far as Istanbul is concerned, its existing organic, unplanned structure leaves its place to a, mostly grid-shaped, planned structure and thus a spatial structure which takes no notice of local features such as climate, topography and orientation, and its immediate surroundings emerges.
Keywords: urban regeneration; urban morphology; gated community; Istanbul; Gaziosmanpasa